Model Tax Avoidance of Indonesian Property Companies within the Perspectives of Size, Sales and Corporate Governance - Baroroh , Niswah; Apriyanti, Rita (KnE Social Sciences, 2020)
This research aims to determine the influences of the company’s size, sales growth, and independent commissioner on the tax avoidance with audit quality as a moderating variable. The population of this research is the property and real estate companies registered on the Indonesia Stock Exchange within the period 2014-2017. The sample is selected using purposive sampling method covering 26 companies. The data analysis tools used are descriptive analysis and multiple linear regression with SPSS version 23. The results of the research show that company’s size and sales growth have a significant and positive effect on the tax avoidance, while the independent commissioner does not show any significant influence. The audit quality moderates the influence of sales growth on the tax avoidance, but it does not moderate the influence of the company size and independent commissioner on the tax avoidance. The future researchers are suggested to use other different proxies to measure the independent commissioner to describe the condition of the company’s independent commissioner. Keywords: Tax Avoidance; Company Size; Sales Growth; Independent Commissioner; Audit Quality